Investigation of the language tasks to include in a short‐language measure for children in the early school years. Issue 4 (18th February 2018) - Matov, Jessica; Mensah, Fiona; Cook, Fallon; Reilly, Sheena
Abstract: Background: The inaccurate estimation of language difficulties by teachers suggests the benefit of a short‐language measure that could be used to support their decisions about who requires referral to a speech–language therapist. While the literature indicates the potential for the development of a short‐language measure, evidence is lacking about which combination of language tasks it should include. Aims: To understand the number and nature of components/language tasks that should be included in a short‐language measure for children in the early school years. Methods & Procedures: Eight language tasks were administered to participants of the Early Language in Victoria Study (ELVS) at ages 5 ( n = 995) and 7 ( n = 1217). These included six language tasks measured by an omnibus language measure (which comprised a direction‐following, morphological‐completion, sentence‐recall, sentence‐formation, syntactic‐understanding and word‐association task) and a non‐word repetition and a receptive vocabulary task, measured by two task‐specific language measures. Scores were analyzed using principal component analysis (PCA), the Bland and Altman method, and receiver operating characteristic (ROC) curve analysis. Outcomes & Results: PCA revealed one main component of language that was assessed by all language tasks. The most effective combination of two tasks that measured this component was a direction‐following and a sentence‐recall task. It showed the greatest agreement with an omnibus language measure and exceeded the criterion for good discriminant accuracy (sensitivity = 94%, specificity = 91%, accuracy = 91%, at 1 SD (standard deviation) below the mean). Conclusions & Implications: Findings support the combination of a direction‐following and a sentence‐recall task to assess language ability effectively in the early school years. The results could justify the future production of a novel short‐language measure comprising a direction‐following and a sentence‐recall task to use as a screening tool in schools and to assess language ability in research participants.